1998
DOI: 10.1038/sj.leu.2400979
|View full text |Cite
|
Sign up to set email alerts
|

Antisense sequences of the nbl gene induce apoptosis in the human promyelocytic leukemia cell line HL-60

Abstract: Apoptosis is induced by the transcriptional inhibitor actinomycin D (Act D) in various cell types, particularly many leukemic cell lines such as HL-60. A common feature of these cell lines is their high constitutive expression level of the nbl gene, which was originally isolated by virtue of its abundance in a Namalwa Burkitt lymphoma cDNA library. In contrast, cell lines which constitutively express nbl at low levels appear not to undergo typical apoptotic death in response to Act D. Apoptotic induction by Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 18 publications
(37 reference statements)
1
27
0
Order By: Relevance
“…The gene encoding RPS3a was down-regulated, and it has been shown that apoptosis is induced in certain cell lines by lowering constitutively high levels of RPS3a expression using antisense RPS3a gene sequences (44). The gene encoding methylthioadenosine phosphorylase was up-regulated.…”
Section: Discussionmentioning
confidence: 91%
“…The gene encoding RPS3a was down-regulated, and it has been shown that apoptosis is induced in certain cell lines by lowering constitutively high levels of RPS3a expression using antisense RPS3a gene sequences (44). The gene encoding methylthioadenosine phosphorylase was up-regulated.…”
Section: Discussionmentioning
confidence: 91%
“…In some experiments, aliquots of 1×10 6 cells/mL were taken after the indicated length of incubation with or without the differentiating agents, and resuspended in fresh media for 6 hours with or without 1µg/mL Act D (Sigma, St Louis, MO, USA) (Naora et al, 1996) or 1µg/ mL A23187 (Boehringer Mannheim GmbH, Mannheim, Germany) . Phosphorothioate oligomers used in the present experiments were the same as those used previously (Naora et al, 1998a). The RPS3a/nbl antisense oligomer contained the sequence complementary to the ATG initiation codon and the next four codons: 5'-CTTGCCAACCGCCAT-3'.…”
Section: Cell Culturementioning
confidence: 99%
“…Briefly, viable cells were identified as those cells that excluded trypan blue dye. Apoptotic cells were identified as those cells which were refractile and showed membrane convolution but still excluded trypan blue dye, whereas those cells whose membrane integrity was compromised and failed to exclude trypan blue dye were considered non-viable (Wyllie et al, 1980;Naora et al, 1996Naora et al, , 1998a. In each experiment, a minimum of 400 cells were counted.…”
Section: Morphological Assessment Of Cell Populationsmentioning
confidence: 99%
See 2 more Smart Citations